Dialysis Patients' and Families' Experiences in Preparing Food at Home - Candra Meriani Damanik; Satriani Hartalina Gultom; Ali Asman Harahap; Syahrul Handoko Nainggolan; Lamtiur Purba (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Kidney failure is one of the diseases that increases every year and becomes a major health problem in the world, the occurrence of failure is a risk of heart and blood vessel disease and increases morbidity and mortality. The purpose of this study was to determine the experience of dialysis patients' families in helping to prepare food at home. The research method used was a qualitative descriptive study. The location of this study was carried out in the Hemodialysis Room of the Imelda Buruh Indonesia General Hospital, Medan . The time of this study conducted in March to July 2024. The number of participants in this study was 6 participants . Research data were collected through in-depth interviews with participants and analyzed thematically. The results of the study consisted of 3 (three) themes, namely: (1) Eating habits , (2) obstacles or challenges in preparing food, (3) family support for patients. The conclusion of this study is that all participants expressed that the eating patterns of patients with hemodialysis therapy showed normal eating patterns, but when hemodialysis was carried out, patients felt weak and their appetite decreased, but all patients still ate 3 times a day in small portions . Overall, participants provided strong support for patients, both moral support, material in efforts to provide patient food needs, reminding patients to eat regularly according to doctor's recommendations, and faithfully accompanying them during hemodialysis. Although obstacles and challenges were found from both patients and families in overall food management, they could be overcome.